Lifestyle Factors and Heart Health: Exploring Effect Modification Using Behavioral Risk Factor Surveillance System Survey Data - Leal, Raeann; Spencer-Hwang, Rhonda; Beeson, W Lawrence; Paalani, Michael; Dos Santos, Hildemar (American journal of lifestyle medicine, 2024)
This study examined the potential relationship between sleep, exercise, and depression with coronary heart disease (CHD) using the 2020 Behavioral Risk Factor Surveillance System (BRFSS) (n = 391 750) during the COVID-19 pandemic. CHD was defined as the presence of self-reported CHD or myocardial infarction (MI). Descriptive statistics were used to report variable frequencies and percentages. Logistic regression models were used to assess potential relationships between lifestyle behaviors (individually and for effect modification) and CHD, with additional sensitivity analysis comparing depressed subjects with non-depressed subjects. Sleep and exercise were assessed in the model for potential effect modification. Those with insufficient sleep and those who did not exercise were more likely to report CHD ( sleep OR = 1.09; 95% CI: 1.06, 1.12); ( exercise OR = 2.00; 95% CI: 1.95, 2.05), though the interaction term was non-significant. Those with self-reported depression were found to be associated with CHD (OR = 1.34; 95% CI: 1.30, 1.38). Among depressed individuals, insufficient sleep and no exercise exhibited a stronger association ( sleep OR = 1.19; 95% CI: 1.13,1.25); ( exercise OR = 2.13; 95% CI = 2.03, 2.23). Results support an association between sleep, exercise, and self-report of CHD, and this association is potentially magnified among depressed individuals, which may be further exacerbated by the COVID-19 pandemic.